Materiality and typology of funerary heritage. The Cemetery of Jesus in Murcia, Spain - Marín-Nicolás, José (2020)
The cemetery of Jesus of Murcia (Spain) has more than 600 pantheons, which converts it in a small funerary city, whose buildings show a large spectrum of architectural samples. This paper presents an exhaustive study of the typologies and materials used in those little buildings. In addition, this investigation addresses the study of the evolution and the distribution of the typologies and materials detected, drawing conclusions about both of these aspects.   Received: 2019-3-15 Revised: 2019-4-22 Accepted: 2019-6-30 Online: 2020-5-4 Publication: 2020-11-27